Design, synthesis of diaminopyrimidine inhibitors targeting IgE- and IgG-mediated activation of Fc receptor signaling. Issue 10 (15th May 2015) - Argade, Ankush; Bhamidipati, Somasekhar; Li, Hui; Sylvain, Catherine; Clough, Jeffrey; Carroll, David; Keim, Holger; Braselmann, Sylvia; Taylor, Vanessa; Zhao, Haoran; Herlaar, Ellen; Issakani, Sarkiz D.; et al.
Graphical abstract: Abstract: Using cultured human mast cells (CHMC) the optimization of 2, 4-diaminopyrimidine compounds leading to22, R406 is described. Compound22 is a potent upstream inhibitor of mast cell degranulation and its mechanism of action is via inhibition of Syk kinase. Compound22 has significant activity in inhibiting both IgE- and IgG-mediated activation of Fc receptor (FcR) in mast cells and basophils, and in addition inhibits Syk kinase-dependent activity of FcR-mediated activation of monocytes, macrophages, neutrophils, and B cell receptor (BCR)-mediated activation of B lymphocytes. Overall, the biological activity of22 suggests that it has potential for application as a novel therapeutic for the treatment of an array of autoimmune maladies and hematological malignancies.